Pengaruh Media Promosi Melalui Tiktokshop Terhadap Minat Beli Mahasiswa Pendidikan Ekonomi Universitas Muhammadiyah Bengkulu - Susanti, Pesi; Suharmi, Suharmi; Selviani, Ayudho (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to 1.) determine the effect of promotional media through TikTok on the purchasing interest of Economics Education Students at the University of Muhammadiyah Bengkulu 2.) to determine the purchasing interest of Economics Education students at the University of Muhammadiyah Bengkulu and to determine the effect of promotional media through TikTok on purchasing interest of Economics Education students at the University of Muhammadiyah Bengkulu. The type of research used is quantitative research. The population in this study was 115 students. The research sample consisted of 34 respondents. The sample used was purposive sampling. Data collection techniques were observation, questionnaires, and documentation. The results of this study, promotional media through TikTok on Economics Education students at the University of Muhammadiyah Bengkulu based on the results of the calculations above are included in the Good category with an average of 36.5 in the interval range (35-42). Purchasing interest in Economics Education students at the University of Muhammadiyah Bengkulu based on the results of the calculations above is included in the interested category with an average of 37.00 in the interval range (35-42). Based on these results, Fsig 0.000 is greater than 0.05 and F count of 57.063 is greater than F table of 3.30, which means HO is rejected and Ha is accepted. Thus, there is a significant influence between online shopping on student spending priorities.